Providing throughput guarantees in heterogeneous wireless mesh networks. Issue 4 (31st January 2012) - de la, Antonio; Banchs, Albert; Serrano, Pablo; Zdarsky, Frank A.
ABSTRACT In this paper, we propose to provide throughput guarantees in heterogeneous wireless mesh networks by jointly optimizing routing and Medium Access Control configuration. Our solution is based on the notion of linearized capacity region, which provides a technology‐independent way of representing the capacity of a wireless link (thereby hiding the technology specifics to the upper layers). From the available capacity of the underlying links as given by the linearized capacity region, we propose two routing algorithms (based on multipath and single path) that find optimal paths for all the flows in the network given their throughput requirements. The throughput allocation resulting from routing is then provided to each link, which uses this information to optimize its technology‐specific Medium Access Control parameters. The proposed approach is evaluated in a heterogeneous scenario comprising Wireless Local Area Networks (WLAN) and Worldwide Interoperability for Microwave Access (WiMAX) technologies and is shown to outperform previous solutions by (at least) a factor of 2.Copyright © 2012 John Wiley & Sons, Ltd.